If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 19x + -4 = 0 Reorder the terms: 10 + -4 + 19x = 0 Combine like terms: 10 + -4 = 6 6 + 19x = 0 Solving 6 + 19x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 19x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 19x = 0 + -6 19x = 0 + -6 Combine like terms: 0 + -6 = -6 19x = -6 Divide each side by '19'. x = -0.3157894737 Simplifying x = -0.3157894737
| (x+4)(y-6)=0 | | 12x+-4+10x+10= | | -15-c=4c | | y+5=4 | | -2x^2+5x+21=0 | | 11c+2=6c+12 | | 123456789x+987654321y=1234569 | | 6h=6y | | 4(1-m)=6 | | 2h=134+8h-362 | | -10x+17=23 | | 17w-9w=6w-20 | | 2(y+6)=12 | | -0.6x=15 | | 57.99+0.11h=58.54 | | -4x+7=-(1+8x)-4(-x+1) | | 7x-5y=20 | | 23=9-2x | | 3x^2=4x+15 | | -30=6(-15) | | (2x-4)-[(x+2)(x-4)]=x^2-4 | | 8x+6(1x+5)=15x-6 | | 100y+60x=320 | | -2x-11x-104=130 | | 45x+23x=1023 | | x+109+x+89= | | -34=x-17 | | 6x+5x+10= | | 8x-2=8(x+7) | | t^2-81u^2=0 | | (r+9)/4=3.5 | | -(x-3)=x+3 |